1991
DOI: 10.1093/cvr/25.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic properties of the ventricular myocardium in cardiomyopathic Syrian hamster, BIO 14.6 strain

Abstract: This study provides the first evidence of the high arrhythmogenicity of the ventricles in cardiomyopathic hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Therefore, we assumed that the hamsters with cardiomyopathy may have died suddenly due to arrhythmias that are frequently associated with the progression of cardiomyopathy. 21) These results suggest that the third-generation β-blocker carvedilol, which acts as a nonselective β-blocker, an β-blocker, and an antioxidant, could prevent cardiac events and thus prolong survival.…”
Section: Survival Ratementioning
confidence: 82%
“…Therefore, we assumed that the hamsters with cardiomyopathy may have died suddenly due to arrhythmias that are frequently associated with the progression of cardiomyopathy. 21) These results suggest that the third-generation β-blocker carvedilol, which acts as a nonselective β-blocker, an β-blocker, and an antioxidant, could prevent cardiac events and thus prolong survival.…”
Section: Survival Ratementioning
confidence: 82%
“…15 Numerous studies have indicated that electrophysiological remodeling such as changes of action potential, K ϩ , and Ca 2ϩ currents occurs in hypertrophy and heart failure (see review by Tomaselli and Marbán 7 ). Thuringer et al 5,6 reported that the I to and I Ca,L densities were decreased and the APD was prolonged in ventricular cells isolated from MS 200 Syrian hamsters in which dilated cardiomyopathy develops without any detectable hypertrophic phase.…”
Section: Matsumoto Et Al Et a Receptor Blockade On Electrical Remodelingmentioning
confidence: 99%
“…12,13 More recently it has been found that long-term treatment with TA-0201, a selective ET A antagonist, 14 improved cardiac function and survival rate in cardiomyopathic Syrian hamsters. 11 Since the BIO 14.6 cardiomyopathic hamsters were reported to have ventricular arrhythmias in the late stage, 15 the ET A receptor antagonist might prevent sudden cardiac death by inhibiting electrophysiological alterations associated with cardiomyopathic contractile dysfunction. Therefore, the present study was undertaken to examine the effect of long-term ET A receptor blockade on the electrophysiological properties of ventricular cells, the surface ECG, and the survival rate in cardiomyopathic Syrian hamsters.…”
mentioning
confidence: 99%
“…Nevertheless, the present data support the view that biochemical and compositional changes occurring in cardiac membranes of cardiomyopathic hamsters could be related with the pathophysiology of the Syrian hamster cardiomyopathy. In fact, an overall defect in membrane composition could lead to the onset of electrolyte imbalance [16,37] in the early stages of cardiomyopathy and, later, to arrhythmias [38] and necrosis of the tissue.…”
Section: Discussionmentioning
confidence: 99%